Childhood acute rheumatic fever in Ankara, Turkey - Özer, Sema; Hallıoğlu, Olgu; Özkutlu, Süheyla; Çeliker, Alpay; Alehan, Dursun; Karagöz, Tevfik (The Turkish Journal of Pediatrics, 2005)
Patients with acute rheumatic fever (ARF) admitted to a tertiary hospital in Ankara between January 1999 and July 2002 were studied cross-sectionally to verify the clinical profile and were followed during the acute period. All patients were investigated for throat culture, streptococcal serologic study, C-reactive protein, and erythrocyte sedimentation rate, and telecardiograms, electrocardiograms and echocardiographic study were done. During the study period, 129 attacks of ARF were observed: 118 were initial attacks and 11 were recurrences. Age on admission was 11.2 +/- 2.73 years (mean +/- SD, range: 6-21 years). Polyarthritis alone was present in 42 cases (33%), carditis alone in 33 (25%), combined carditis and polyarthritis in 36 (28%), combined carditis and chorea in 15 (12%) and chorea alone in 3 (2%). Nineteen (14%) patients with isolated arthritis and pure chorea had silent mitral and/or aortic regurgitation. Carditis was a dominant presenting manifestation, but appeared to be mild or moderate. The present study indicates that ARF is still a significant problem in Turkey. The observation that 8.5% of the attacks were recurrent reaffirms the need for more effective secondary prevention programs.